2019
DOI: 10.1097/acm.0000000000002999
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Debriefing: A Qualitative Study of Event Reconstruction at an Academic Medical Center

Abstract: Purpose This qualitative study sought to characterize the role of debriefing after real critical events among anesthesia residents at the Hospital of the University of Pennsylvania. Method From October 2016 to June 2017 and February to April 2018, the authors conducted 25 semistructured interviews with 24 anesthesia residents after they were involved in 25 unique critical events. Interviews focused on the experience of the event and the interactions tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…This mixed-methods study was followed up with a qualitative study that further explored the interviews with anesthesia residents after actual critical events. 60 The interviews revealed that debriefing for the residents, in the setting of real events, was considered part of a multistage process that included internal dialogue, event documentation (as a component of reconstructing what happened), and lessons they felt they learned (not necessarily in this order or with distinct borders). In each stage of this process, there were residents who were self-negotiating their perceived reputation, affective response, and extent to which they internally felt culpable for what had happened.…”
Section: Part Ii: the Landscape And Scarcity Of This Practice After Amentioning
confidence: 99%
See 1 more Smart Citation
“…This mixed-methods study was followed up with a qualitative study that further explored the interviews with anesthesia residents after actual critical events. 60 The interviews revealed that debriefing for the residents, in the setting of real events, was considered part of a multistage process that included internal dialogue, event documentation (as a component of reconstructing what happened), and lessons they felt they learned (not necessarily in this order or with distinct borders). In each stage of this process, there were residents who were self-negotiating their perceived reputation, affective response, and extent to which they internally felt culpable for what had happened.…”
Section: Part Ii: the Landscape And Scarcity Of This Practice After Amentioning
confidence: 99%
“…This mixed-methods study was followed up with a qualitative study that further explored the interviews with anesthesia residents after actual critical events. 60 The interviews revealed that debriefing for the residents, in the setting of real events, was considered part of a multistage process that included internal dialogue, event documentation (as a component of reconstructing what happened), and lessons they felt they learned (not necessarily in this order or with distinct borders). In each stage of Box 2 Lessons from selected medical literature not specific to anesthesiology on the landscape and scarcity of debriefing after actual critical events A national survey of pediatric emergency medicine fellows regarding critically ill children in the emergency department (ED) showed that 99% of respondents had participated in medical resuscitations during their fellowship, yet more than 30% indicated that they had never participated in a debriefing session afterward; the majority estimated that postresuscitation debriefing in the ED took place 50% or less of the time.…”
Section: Part Ii: the Landscape And Scarcity Of This Practice After Actual Critical Eventsmentioning
confidence: 99%
“…Demian Szyld , 1,2,3 Alexander F Arriaga 3,4,5,6 Critical event debriefing (CED) or 'hot debriefings' (HoDs) can be described as a trigger-based, immediate postevent, interprofessional, expertly facilitated conversation where clinicians recount, reflect on, and improve personally and as a team. 1 The process and experience of clinicians who cared for the patient is more complex and involves thoughts and emotions that go beyond the 'case' or 'resuscitation' and the debriefing itself.…”
Section: Implementing Clinical Debriefing Programmesmentioning
confidence: 99%
“…1 The process and experience of clinicians who cared for the patient is more complex and involves thoughts and emotions that go beyond the 'case' or 'resuscitation' and the debriefing itself. 2 The American Heart Association guidelines for neonatal resuscitation highlight 'team debriefing' as a key step in their cognitive aid. 3 There is evidence that implementing a 'Cold Debrief ' programme for teams that care for patients in cardiac arrest improves outcomes 4 yet in practice 33% of events are routinely debriefed.…”
Section: Implementing Clinical Debriefing Programmesmentioning
confidence: 99%
“…However, many clinicians and educators report to struggle with leading debriefings 22 23. In spite of the versatile supply of tools for creating and maintaining inviting debriefing conditions,24–26 structuring debriefings7 27–37 and managing challenging debriefing situations,25 38 facilitating debriefings is perceived as difficult 22 23 39 40.…”
Section: Introductionmentioning
confidence: 99%